ANALISIS LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR KELURAHAN PEKOJAN JAKARTA BARAT - Diva Alfajriyati Sabil; Agustina Mogi (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of the work environment on employee performance in Pekojan Village, West Jakarta. With office locations located in densely populated residential areas and often facing noise interference from outside, this research focuses on how working environmental conditions, both physical and non-physical, affect employee productivity. The research method used is a qualitative method with a descriptive approach. Data collection was carried out through in-depth interviews with 10 Pekojan Village employees as informants. Apart from that, field observations were also carried out to find out directly the conditions of the work environment. The research results show that noise from the surrounding environment is one of the biggest challenges that affects employee concentration and work effectiveness. Lack of supporting facilities such as a comfortable work space is also an obstacle. However, harmonious working relationships and high motivation from employees help reduce this negative impact. This research recommends improving work facilities, installing sound dampeners as a solution to increase employee productivity. A conducive work environment, both physical and non- physical, is very influential in improving employee performance. With continuous improvement, it is hoped that public services in Pekojan Village can be more optimal.